The Portrayal of American Indian Identity in The Lone Ranger and Tonto Fistfight in Heaven - Firdaus, Ahmad Fanan (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study delved into the cultural identity of American Indians residing in the Spokane reservation area, with a focus on Sherman Alexie's collection of stories, "The Lone Ranger and Tonto Fistfight in Heaven." The stories portrayed various aspects of the divide between American Indians and white people, as well as the distinctions between reservation-based Indians, urban Indians, modern Indians, and traditional Indians. The main objective of the research was to explore how the identity of American Indians is depicted in Alexie's book using Homi K Bhabha's cultural identity theories of hybridity and mimicry. This study employed the literary criticism method, particularly postcolonial studies, to analyze the representation of hybridity and mimicry. The primary data source for this investigation was the collection of short stories, "The Lone Ranger and Tonto Fistfight in Heaven," by Sherman Alexie. The data was gathered from the text, identifying words or sentences that illustrate the representation of hybridity and mimicry in the stories. The data collection techniques include reading and note-taking strategies. This study revealed two main aspects of Indian cultural identity: Hybridity, characterized by a blend of Indian and white culture, evident in language, behavior, ways of thinking, and lifestyles. Then Mimicry, seen in Indian behavior, lifestyle, and ways of thinking that resemble those of white people. In conclusion, the research highlighted how Indian cultural identity in Sherman Alexie's work reflects both hybridity and mimicry, shedding light on the complexities of cultural assimilation and adaptation in American Indian communities.